Robotic Surgery for Rectal Cancer Treatment: Clinical Outcomes and Quality of Life. Comparison of Surgical Methods - Akelaitytė, Raminta; Žilinskas, Justas (Lietuvos chirurgija, 2025)
Background. Rectal cancer is one of the most common oncological diseases in the world. In recent years, robotic surgery has been increasingly used to improve the outcome of this disease. Aim. To review the latest scientific literature on the application of robotic surgery in the treatment of rectal cancer and to evaluate clinical outcomes in patients. Material and methods. The research method is a literature review. Publications were researched in the PubMed and Google Scholar databases using the following keywords and their combinations in English: rectal cancer, robotic surgery, laparoscopic surgery, open surgery. Based on the inclusion and exclusion criteria, 68 scientific publications were included in the review. Results. The average duration of robotic surgery was longer (164.5±47.5–275±60.5 minutes) and was more expensive than other surgical methods. However, patients recovered faster, lost less blood and the hospitalization was shorter (on average 7 days), complications (7.7–22.1%) and local recurrences (0–8.3%) were less frequent and this surgery had better survival rates. The incidence of R0 resection was 90.3–100%, while the incidence of distant metastases was 0–21.1%. No deaths were recorded during the surgery. Conclusions. Robotic surgery is a safe and effective method for treating rectal cancer. It is associated with a lower risk of bleeding, shorter hospitalization, fewer local recurrences, fewer post-operative complications, faster recovery and better quality of life in the long term but requires more economic resources than other surgical approaches.